Latin America and Caribbean Poverty and Labor Brief, August 2012 : The Effect of Women's Economic Power in Latin America and the Caribbean - World Bank (Washington, DC, 2012)
For the last decade, economic growth in Latin America and the Caribbean (LAC) has sharply accelerated, pushing poverty and inequality to historic lows in the most unequal region in the world. In 2012, as the world’s ongoing economic problems make optimistic predictions less certain and threaten to undermine gains against poverty and inequality, it is critical to understand the structural forces that have promoted recent positive social outcomes. This report explores how women in the region have played a critical role in achieving the poverty declines of the last decade, with their labor market participation rates growing 15 percent from 2000 to 2010. It further considers how future progress will require increased female economic power and more effective policies to promote it. If female labor income had remained the same during this period, holding all else constant, extreme poverty in Latin America and the Caribbean would have been 30 percent higher in 2010. In other words, 17.7 percent of the population in the region would have been below the extreme poverty rate, compared to the actual 14.6 percent. The report suggests focusing public policy on three priorities: expanding female labor market opportunities; improving female agency which — while important in its own right — has important potential benefits for equality of economic opportunities and assets, and supporting the growing number of poor single female-headed households. Along with these suggested policy priorities, strong monitoring and evaluation systems should be included to every extent possible.